Occupational safety and health risk management in pineapple plantation - Sukadarin, Ezrin Hani; Aziz, Hanida Abdul; Zakaria, Junaidah; Joharizal, Johari; Mimi Nabila, Mohd Noordin; Mohamad Hafizi, Che Mat; Mohd Shamsul Azmi, Samsudin; Mohd Fauzan, Mohd; Nur Fazrina, Mohd Salleh (2017)
Risk management in the agricultural setting are considered an important element in rising up the quality of working life among workers. A descriptive cross sectional study had been conducted at Rompine Integrated Pineapple Plantation (RIPP) to disseminate knowledge to workers and management in relation to occupational safety and health (OSH) risk management. A series of data collection activities had been conducted through a walkthrough observation, interviews and video recording. Subsequently, the research team had developed and delivered a comprehensive four units’ module from February to August 2017. This module had been developed clearly based on the identified issues or problems at the pineapple plantation. A number of 10 identified hazards had been analysed and were added to the module mainly to be discussed and clarify to the audience emphasizing on way how to reduce the risk. Two hours of face to face lecturing session were performed by the instructors for each module. Notably, it is proven that audience had improved their knowledge and awareness after the session finish. Knowledge and awareness of occupational safety and health had been transferred through these four modules to the audience. It can be shown through their willingness to perform safe work practice as well as to participate in activities related to safety and health awareness such as campaign and group discussion. The successful of the knowledge transfer program (KTP) at RIPP also spread to other branches of pineapple plantation under Malaysia Pineapple Industry Board (MPIB). The awareness on OSH among top management was improved. The demand on OSH training and education in multiple state also increased. It was indirectly improved MPIB reputation local and globally. In conclusion, workers and management team had successfully increased their knowledge and awareness towards safety and health issues arises at their plantation, by participating in the four units modules developed. Indeed, results from this positive outcome had increase generally the economic gain and pineapple production capability in RIPP.